Effects on Plants of Metabolites Produced in Culture by «Phaeoacremonium chlamydosporum», «P. Aleophilum» and «Fomitiporia punctata» - Graniti, Antonio; Bruno, Giovanni; Sparapano, Lorenzo (Phytopathologia Mediterranea, 2000)
Several phytotoxic metabolites were extracted and purified from culture filtrates of Phaeoacremonium chlamydosporum, P. aleophilum and Fomitiporia punctata, three fungi associated with esca of grapevine. Those identified and characterised so far were a-glucans of various molecular weight (pullulans) produced by both species of Phaeoacremonium, and two naphthalenone pentaketides (scytalone and isosclerone) produced by P. aleophilum. Absorbed at very low doses by detached leaves of grapevine or injected into the woody tissue of shoots and branches of standing grapevines, these metabolites produced foliar symptoms similar to those shown by the esca-affected vines. The same results were obtained with preparations of pullulan extracted from the discoloured woody tissue of a grapevine infected with P. chlamydosporum, and with samples of commercial pullulan.